Plasmonic Au/TiO2‐Dumbbell‐On‐Film Nanocavities for High‐Efficiency Hot‐Carrier Generation and Extraction. (10th July 2018) - Ho, Kwun Hei Willis; Shang, Aixue; Shi, Fenghua; Lo, Tsz Wing; Yeung, Pui Hong; Yu, Yat Sing; Zhang, Xuming; Wong, Kwok‐yin; Lei, Dang Yuan
Abstract: Plasmon‐induced hot carriers have vast potential for light‐triggered high‐efficiency carrier generation and extraction, which can overcome the optical band gap limit of conventional semiconductor‐based optoelectronic devices. Here, it is demonstrated that Au/TiO2 dumbbell nanostructures assembled on a thin Au film serve as an efficient optical absorber and a hot‐carrier generator in the visible region. Upon excitation of localized surface plasmons in such coupled particle‐on‐film nanocavities, the energetic conduction electrons in Au can be injected over the Au/TiO2 Schottky barrier and migrated to TiO2, participating in the chemical reaction occurring at the TiO2 surface. Compared with the same dumbbell nanostructures on an indium tin oxide (ITO) film, such nanocavities exhibit remarkable enhancement in both photocurrent amplitude and reaction rate that arise from increased light absorption and near‐field amplification in the presence of the Au film. The incident‐wavelength‐dependent photocurrent and reaction rate measurements jointly reveal that Au‐film‐mediated near‐field localization facilitates more efficient electron–hole separation and transport in the dumbbells and also promotes strong d‐band optical transitions in the Au film for generation of extra hot electrons. Such nanocavities provide a new plasmonic platform for effective photoexcitation and extraction of hot carriers and also better understanding of their fundamental science and technological implications in solar energy harvesting. Abstract : A Au/TiO2 ‐dumbbell‐on‐Au‐film‐nanocavity system is presented herein. This system features a dual hot electron injection channel recognized as an efficient localized plasmon resonance mechanism and a d‐band optical transition mechanism.